2022
DOI: 10.1186/s12903-022-02613-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of implant site preparation with piezosurgery versus conventional drills in terms of operation time, implant stability and bone density (randomized controlled clinical trial- split mouth design)

Abstract: Background The preparation of the implant bed has a major influence on the success rate and long-term survival of dental implants. Piezoelectric devices and special implant drilling inserts are now emerging to replace conventional drills showing improved bone response and healing around implants. The purpose of this study is to compare the piezoelectric inserts versus the traditional drills for implant site preparation. Methods Twelve male patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Furthermore, the movement of the TD is not constant. The creation of the implant site is a direct outcome of erosion, characterized by an elliptical pattern, leading to areas of bone deficiency [42]. The MM is not subject to this limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the movement of the TD is not constant. The creation of the implant site is a direct outcome of erosion, characterized by an elliptical pattern, leading to areas of bone deficiency [42]. The MM is not subject to this limitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the maximum temperature that living tissue can withstand has been determined as 50 ˚C. In line with similar studies and information, the temperatures chosen to simulate both hot and cool oral environments were 25 and 50 ˚C [59,60]. To simulate acidic beverage environments, 0.9 wt% NaCl solutions at pH 3 and 5 were prepared using lemon juice.…”
Section: Methodsmentioning
confidence: 99%
“…A few histomorphometrical, immunohistochemical, and molecular analysis comparing piezosurgery with conventional drills and oscillating saws observed similar rate of bone healing but slightly more bone formation following piezosurgery. 46 Bone harvested using PS device was found to contain more osteoblast like cells. 47 Stubinger et al observed better periosteal microcirculation while using PS device for subperiosteal preparation which could be an incentive for enhanced bone metabolism.…”
Section: Disscusionmentioning
confidence: 95%